Hypoglycaemia associated with co-trimoxazole use in a 56-year-old Caucasian woman with renal impairment. (9th November 2012) - Forde, Donall G; Aberdein, Jody; Tunbridge, Anne; Stone, Ben
Abstract : Here we present a case of refractory hypoglycaemia associated with use of the antibiotic trimethoprim-sulfamethoxazole (TMP-SMX). This was used to treat Pneumocystis jirovecii pneumonia (PCP) infection. The patient had significant pre-existing renal impairment with a kidney transplant in situ. Refractory hypoglycaemia occurred 5 days after starting the antibiotic and persisted for 36 h after its cessation. SMX contains the same sulphanilamide structural group as the oral hypoglycaemic agents called sulphonureas. SMX could therefore act as an insulin secretagogue. The inappropriately raised insulin and c-peptide levels seen in our patient support this theory. The 5-day asymptomatic period would allow sufficient time for the drug to accumulate and the extended period seen after its cessation would be seen in a dose-dependent side effect. Following 3 days of observation and continuous glycaemic support on the High Dependency Unit she was discharged back to the ward, with no further occurrence of hypoglycaemia.